Evaluation of Green Marketing Strategy Using Fuzzy AHP-Based Decision Support System - Marsono Marsono; Asyahri Hadi Nasyuha; Evi Rosalina Widyayanti; Meng-Yun Hadi Chung (Sinkron : jurnal dan penelitian teknik informatika, 2026)
Growing environmental awareness among consumers has encouraged companies to integrate ecological considerations into their marketing activities. However, many firms still find it difficult to determine which green marketing strategy should be prioritised, because the decision involves multiple conflicting criteria and a high degree of subjective human judgment. This study designs and applies a decision support system based on the fuzzy analytic hierarchy process (FAHP) to evaluate and rank green marketing strategy alternatives for a consumer goods company. The decision problem was structured into a three-level hierarchy consisting of the main goal, five evaluation criteria, namely green product, green price, green promotion, green distribution, and green corporate image, and four strategy alternatives. Expert judgments were gathered through pairwise comparison questionnaires using linguistic variables that were converted into triangular fuzzy numbers. Chang’s extent analysis was applied to compute the fuzzy synthetic extent and the degree of possibility, and the priority weights were normalised and verified through a consistency check (CR = 0.095, below the 0.10 threshold). To strengthen the validity of the recommendation, the alternative ranking obtained from FAHP was cross-validated against the Simple Additive Weighting (SAW) and TOPSIS methods. The results indicate that green product is the most important criterion (0.327), followed by green promotion (0.277) and green corporate image (0.210), while sustainable packaging is identified as the most preferred strategy alternative (0.294). All three methods produced an identical ranking, and a sensitivity analysis confirmed that the ranking remained stable under reasonable variations in the criteria weights. The proposed decision support system, whose architecture and interface are also presented, offers a transparent, consistent, and reproducible tool that helps managers allocate resources to the most effective green marketing strategy.